The Impact of Corporate Social Responsibility on Quality Health, Safety and Environment - Abderraouf, Guembour; Dr. Raki Nadira (European Journal of Multidisciplinary Studies, 2018)
This article aims to identify the role of corporate social responsibility in influencing quality health, safety and environment in the organization. From this point, this study tries to drive the thinking of economic companies that taking benefits from quality, health, safety and environment, requires their good management inside the organization. For that the companies needs to focus on good corporate social responsibility. Therefore, we are trying through this article to clarify the impact of corporate social responsibility on quality, health, safety and environment. In addition, among the most important results reached in this intervention, is that the meaning of QHSE is more than just looking on quality of products and services, and ensuring health - safety - environment, its real objective is gaining the customer satisfaction, ensuring the resources conservation and environment protection in the production process gaining social satisfaction, and gaining the employee satisfaction. Corporate Social Responsibility reflects the social imperatives and the social consequences of business success. Moreover, CSR can improve QHSE practices by following Total Quality management principles in order to ensure quality, helping healthcare organizations in the provision of health care in rural and remote areas in order to ensure health - safety, and reduce the consumption of raw materials and energy, reduce production of hazardous waste and pollution in order to ensure environment.